"Those who eat from one pot": Constructing household as a social category in a cash transfer programme in Ghana. (30th November 2021) - Puorideme, Dennis; Christensen, Ivan Lind
Abstract: Social categorisation is situated at the core of any modern attempt to govern or intervene in the social world. This paper investigates the construction of the concept of household in Ghana's official social statistics and its implications when implemented in the internationally co‐organised cash transfer programme, the Livelihood Empowerment Against Poverty (LEAP) programme. The study is based on various literature, conceptual analysis and interviews with key stakeholders, including the LEAP programme authorities and focal persons in a local community. The findings indicate discrepancies between the category of household and the cultural setting it is meant to represent in the Ghanaian context.